Novel Norovirus in Dogs with Diarrhea - Mesquita, João Rodrigo (Centers for Disease Control and Prevention, 2010)
To identify the prevalence and genetic variability of noroviruses in dogs, we tested fecal samples by using reverse transcription–PCR. We found canine norovirus in 40% and 9% of dogs with and without diarrhea, respectively. The virus was genetically unrelated to other noroviruses and constitutes a tentative new genogroup.